Compliance Rate Of Surgical Information Systems With The Information Needs Of Surgeons 2012 - Maryam Ahmadi; Masume Khoshgam; Akram Farhadi (Tehran University of Medical Sciences, 2013)
Background and Aim: Considering the information needs of users improves the quality of care . We aimed to Survey the Compliance Rate of Surgical Information Systems with The Information Needs of surgeons. Materials and Methods: This was a descriptive and original study. Statistical Society consisted of two groups. First was the hospital information systems in hospitals of Tehran University of Medical Sciences and Shahid Beheshti were the first group. The Second group were 982 surgeons. Hospitals that had the highest number of surgeries were the research sample. Researcher gathered data in two steps. First by questionnaire and then checklist was used to collect the data by interviewing the technicians' of systems . All data has been analyzed by descriptive analysis. Results: In Rasul and Emam hospitals surgical information systems in scheduling section(50%) had highest conformity with surgeons needs. In flexibility section in all hospitals except of Shariati, they had 50% conformity with information needs of surgeons. Conclusion: From surgeons view flexibility capability, scheduling and accessing data had highest priority although systems from display capability had not the conformity with the user needs. In designing the surgical information systems in future it is better to consider these capabilities.